ANALISIS RESEPSI PEMBACA CERPEN “KOROSHIYA DESUNOYO” KARYA HOSHI SHIN’ICHI (STUDI KASUS TERHADAP 15 ORANG JEPANG) - Wati, Noor Rahmi (Japanese Literature, 2013)
This thesis research about literary reception. Literary reception is a study of reader response to literature. In reviewing and discussing literature for example novels or short stories, there are two kinds of readers. The expert readers and amateur readers. This thesis is an analysis of the literary reception of the response amateur reader with the number 15 Japanese respondents in view of a Japanese short story entitled "Koroshiya Desunoyo" by Hoshi Shin'ichi. The aim of this research is to describe the response or reception of respondents to the short story. The limit issues to be discussed are reception of respondents to the elements contained in the structure builder of the short story “Koroshiya Desunoyo” by using the method of reception of literature, sociology of literature and structural. The results to be achieved in this research is to know how much respondents understanding of the short story "Koroshiya Desunoyo" and to see the reception of respondents to the elements of the short story structure builder. Keywords : Literary reception, amateur reader, structure builder.